2014
DOI: 10.1159/000358404
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Based Study of Mucopolysaccharidosis Type VI in Brazil: The Influence of Founder Effect, Endogamy and Consanguinity

Abstract: Mucopolysaccharidosis type VI (MPS VI - Maroteaux-Lamy syndrome) is a globally rare lysosomal storage disease caused by a deficiency of arylsulfatase B. However, in Monte Santo, a poor and isolated rural region in Northeast Brazil with large family sizes and high rates of community endogamy and parental consanguinity (α = 0.00483), 9 living and 4 now deceased individuals in 11 kindreds have been diagnosed with MPS VI, all with the same p.H178L missense founder mutation. A further 33 deceased persons have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 22 publications
(26 reference statements)
2
30
0
2
Order By: Relevance
“…Most patients with a history of consanguinity were from the Southeast and Northeast regions. In the latter, previous studies have reported high rates of consanguinity in specific areas of such states as Bahia (Costa‐Motta et al, ), Paraíba (Weller et al, ) e Rio Grande do Norte (Santos et al, ). According to a March of Dimes report, an estimated 1 to 10% of unions in South America are consanguineous (Christianson, Howson, & Modell, ), a rate far below that found in the present study and in the aforementioned investigations.…”
Section: Discussionmentioning
confidence: 95%
“…Most patients with a history of consanguinity were from the Southeast and Northeast regions. In the latter, previous studies have reported high rates of consanguinity in specific areas of such states as Bahia (Costa‐Motta et al, ), Paraíba (Weller et al, ) e Rio Grande do Norte (Santos et al, ). According to a March of Dimes report, an estimated 1 to 10% of unions in South America are consanguineous (Christianson, Howson, & Modell, ), a rate far below that found in the present study and in the aforementioned investigations.…”
Section: Discussionmentioning
confidence: 95%
“…Lastly, all 14 homozygote subjects with the variant p.(His178Leu) are Brazilian, and belong to a cluster of MPS VI patients living in Northeast Brazil. These subjects all show the same haplotype (Costa‐Motta et al., ), which is likely due to a founder effect, with the contemporary presence of parental consanguinity and endogamy.…”
Section: Variantsmentioning
confidence: 90%
“…The prevalence of MPS VI varies among populations, with estimates ranging from 0.0132 per 100,000 live births in Poland to 8.0 per 100,000 live births in Saudi Arabia to 20.0 per 100,000 live births in Monte Santo, a small town in Brazil (Costa‐Motta et al., ; Jurecka, Ługowska, Golda, Czartoryska, & Tylki‐Szymańska, ; Moammar, Cheriyan, Mathew, & Al‐Sannaa, ; Vairo et al., ). While several variables likely influence prevalence rates across populations, it is expected that populations with higher degrees of consanguinity display a higher prevalence of the disease (Baehner et al., ; Costa‐Motta et al., ). Importantly, disease prevalence is likely underestimated in all populations since these epidemiological studies generally rely on clinical identification of disease rather than prenatal or newborn screening (Valayannopoulos et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Hastalık klinik olarak heterojendir. Hastaların çoğunda hızlı ilerleyen form mevcut iken, az bir kısmında ise yavaş ilerleyen form mevcuttur (4). Yapılan uluslararası çalışmalarda, MPS tip VI insidansının Almanya'da yaşayan Türk toplumunda 1: 43,261, İsveç'te 1: 1,505,160 arasında değişen oranlarda olduğu belirtilmiştir (5).…”
Section: Introductionunclassified
“…Brezilya'da ve Brezilya'ya pek çok kişinin göç ettiği Portekiz'de, genel MPS dağılımı düşünüldüğünde, MPS tip VI'nın oransal olarak arttığı rapor edilmiştir (7,8). Örnek olarak; Brezilya'nın Monte Carlo şehrine bağlı Bahia eyaletinde, MPS VI prevelansı 1: 5,000 olarak yayınlamış ve bunun sebebi muhtemelen tüm olgularda tek mutasyonun varlığı (p.H178L) ve kabile içi evlenmenin kombinasyonu olarak gösterilmiş (4).…”
Section: Introductionunclassified